KINERJA KELEMBAGAAN KELOMPOK TANI HUTAN KEMASYARAKATAN DI KABUPATEN TANAH LAUT - Boyke Wijaya; Hamdani Fauzi; Hafizianor Hafizianor (Jurnal Sylva Scienteae, 2020)
The purpose of this study is to inventory and analyze the institutional performance factors of community forest farmer groups in Tanah Laut district. The expected benefit of this research is to be able to provide data and information on the existing conditions of the KTH HKm institutional performance so that appropriate strategies, facilitation and policies can be carried out to improve and or maintain the institutional performance of the HK KTH. The method used is a 30% random sampling method for 14 populations and a KTH HKm sample. Starting from determining the sample, taking data in the field, processing data and reporting the results of research. The data collected is divided into primary data (farmer group institutional performance data) and secondary data (various literature related to research and physical data such as questionnaires). The results of the study showed that the farmer group Want To Go Forward into the performance class was very good, the Sukamaju farmer group entered the performance class very well, the farmer group Subur Makmur entered the performance class enough and the Harapan Baru farmer group had a good performance class.Keyword: farmer group institutional performance; community forestry